Analysis of Mathematical Problem Solving Skills using Meta-Cognitive Strategy from The Perspective of Gender-Based Self-Efficacy - Mufida, Aina; Suyitno, Hardi; Marwoto, Putut (Unnes Journal of Mathematics Education Research, 2018)
This research aims to analyze the effect improved self-efficacy in students’ ability to solve mathematical problems from the gender perspective with the implementation of meta-cognitive strategy for the topic of prism and pyramid. It is a mixed method research using the concurrent embedded model. Subjects involved were students of Class VIII (eighth grade) of MTs Asy-Syarifah Mranggen (Islamic Junior High School of Mranggen). It is found in the field that when students have to deal with applied mathematics concerning everyday life problems of significant difficulty level, they are not confident about their own abilities to solve them. Results show that 1) Self-efficacy greatly influences students’ ability in solving mathematical problems; 2) At the same level of self-efficacy, boys and girls undergo the same process and get the same results in terms of mathematical problem solving skills; 3) Students have different levels of ability in solving mathematical problems based on self-efficacy; 4) There has been an increase in self-efficacy prior to and after the implementation of met-cognitive strategy for the topic of prism and pyramid.